2011
DOI: 10.1111/j.1365-313x.2011.04707.x
|View full text |Cite
|
Sign up to set email alerts
|

Cell autonomous and cell‐type specific circadian rhythms in Arabidopsis

Abstract: SUMMARYThe circadian system of plants regulates a wide range of rhythmic physiological and cellular output processes with a period of about 24 h. The rhythms are generated by an oscillator mechanism that, in Arabidopsis, consists of interlocking feedback loops of several components including CIRCADIAN CLOCK ASSOCIATED 1 (CCA1), LATE ELONGATED HYPOCOTYL (LHY), TIMING OF CAB EXPRESSION 1 (TOC1) and CCA1 HIKING EXPEDITION (CHE). Over recent years, researchers have gained a detailed picture of the clock mechanism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
73
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(89 citation statements)
references
References 51 publications
10
73
0
3
Order By: Relevance
“…It is noteworthy that mathematical modeling suggests that the difference in clock properties between the shoot and root can be explained by light sensitivity of clock entrainment in each tissue (Bordage et al, 2016). Supporting this idea, tissue-specific clock properties, such as phase variation in clock genes, or different sensitivity to temperature signals, has been reported in intact Arabidopsis plants (Thain et al, 2002;Michael et al, 2003;Yakir et al, 2011). Recent tissue-specific microarray time-course analysis revealed that the clock genes in mesophyll cells and vascular cells show distinct expression profiles from each other ( Fig.…”
Section: Tissue Specificity In Clock Functionmentioning
confidence: 62%
“…It is noteworthy that mathematical modeling suggests that the difference in clock properties between the shoot and root can be explained by light sensitivity of clock entrainment in each tissue (Bordage et al, 2016). Supporting this idea, tissue-specific clock properties, such as phase variation in clock genes, or different sensitivity to temperature signals, has been reported in intact Arabidopsis plants (Thain et al, 2002;Michael et al, 2003;Yakir et al, 2011). Recent tissue-specific microarray time-course analysis revealed that the clock genes in mesophyll cells and vascular cells show distinct expression profiles from each other ( Fig.…”
Section: Tissue Specificity In Clock Functionmentioning
confidence: 62%
“…The region of 1,140 bp of the GC1 promoter that has been shown to define guard cell expression (Yang et al, 2008) was synthesized by GenScript. The construct was cloned into pMLBART, and plants were transformed and selected as described in Yakir et al (2011).…”
Section: Transgenic Plantsmentioning
confidence: 99%
“…In addition to transcriptional regulation, there is increasing evidence of other layers of regulation of oscillator components such as chromatin remodeling and protein modification (reviewed in Seo and Mas, 2014). It is likely that almost every cell in the plant has its own oscillator mechanism and the extent to which these oscillators are coupled is being explored Endo et al, 2014;Fukuda et al, 2007;Yakir et al, 2011;Thain et al, 2000;Wenden et al, 2012). There is also increasing evidence that the model of the Arabidopsis oscillator that has been widely described is an average of the oscillator mechanisms in the whole plant and that different tissues and cells, including stomatal guard cells, may have distinctive variations of the "average" mechanism (Endo et al, 2014;Para et al, 2007;James et al, 2008;Yakir et al, 2011;Takahashi et al, 2015).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To understand the role of [Ca 2+ ] cyt in the circadian network, it is necessary to determine specifically in which cells [Ca 2+ ] cyt functions in the circadian clock. All plant cells are believed to have circadian rhythms that are cell autonomous Yakir et al, 2011). There is evidence of tissue-specific circadian behavior; for example, the vascular bundle circadian clock appears to have a different genetic architecture compared with other tissues (Para et al, 2007).…”
Section: Localization Of Nycthemeral and Circadian Oscillations Of [Cmentioning
confidence: 99%